Trade policy and export diversification in Nigeria in the years 1970-2017: A sectoral analysis - Philip Ifeakachukwu Nwosa; Oluwadamilola Tosin Fasina (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: This study examines the impact of trade policy on export diversification of economic sectors in Nigeria over the period of 1970 to 2017. Research Design & Methods: The study utilises Autoregressive Distributed Lag (ARDL) technique and the Herfindal formula to compute the export diversification index. Findings: The results of the study show that trade policy has a significant impact on export diversification of the oil sector, while the impact of trade policy on export diversification of the remaining sectors of the economy is insignificant. Implications & Recommendations: The Nigerian export base is still highly skewed towards oil export at the expense of other sectors. Thus, with exception to the oil sector, trade policy has not enhanced export diversification of other sectors of the Nigerian economy. Thus, the study recommends that the government de-emphasises dependency on oil and discoveries of new oil wells, such as those discovered in the Southwest and Northern regions of Nigeria. Contribution & Value Added: This study contributes to the literature by showing that trade policy has diverse influence on export diversification in various sectors of the economy. Hence, the use of trade policy recommendations from aggregate analysis should be discontinued while sector specific policies should be adopted.
Keywords: F10; F13; O20; O24; 330; trade liberalization; trade openness; export diversification; bound cointegration; Nigeri